2012
DOI: 10.1590/s0034-737x2012000100019
|View full text |Cite
|
Sign up to set email alerts
|

Potencial alelopático de plantas de cobertura verde de inverno sobre o crescimento do porta-enxerto VR043-43

Abstract: Allelopathic effects of winter cover crops on the growth of the grapevine rootstock VR043-43In recent years, the use of green manure in vineyards has increased significantly. Green manure has been shown to be effective in soil fertility maintenance and erosion control, increasing soil macro and microporosity by penetration and decomposition of roots, increasing organic matter levels, besides the possibility of reducing herbicide usage in vineyards. A number of cover crop species have been used without knowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…Bianchi et al (2011) highlight the importance of R. sativus as weed species when competing with soybean varieties, and identified that some varieties are less affected by competition with this weed species than others. As a plant suppressor, Bettoni et al (2012) reported no allelopathy of extracts of R. sativus on the establishment of Vitis vinifera. On the other hand, Uygur et al (1990) reported that extracts of R. sativus completely inhibited the germination of 4 crop plants and 11 weed species; Inderjit & Mallik (2002) also highlight some allelopathic effects of this weed species.…”
Section: Resultsmentioning
confidence: 99%
“…Bianchi et al (2011) highlight the importance of R. sativus as weed species when competing with soybean varieties, and identified that some varieties are less affected by competition with this weed species than others. As a plant suppressor, Bettoni et al (2012) reported no allelopathy of extracts of R. sativus on the establishment of Vitis vinifera. On the other hand, Uygur et al (1990) reported that extracts of R. sativus completely inhibited the germination of 4 crop plants and 11 weed species; Inderjit & Mallik (2002) also highlight some allelopathic effects of this weed species.…”
Section: Resultsmentioning
confidence: 99%
“…No muchos de los ensayos de laboratorio prestan atención a los factores edáficos y climáticos, la ecología microbiana, la dinámica de nutrientes, la densidad y otras características bióti-cas de la planta agresiva (Inderjit & Weston, 2000), por lo que resulta difícil comprobar su incidencia bajo condiciones de campo. En algunos casos se han encontrado efectos alelopáticos de coberturas verdes sobre porta-injertos de vid, pero utilizando extractos vegetales obtenidos en laboratorio (Bettoni et al, 2012). Inderjit & del Moral (1997) afirman que es esencialmente imposible separar alelopatía de competencia por recursos en los sistemas naturales, y que cualquier esfuerzo por separarlos bajo condiciones experimentales creará condiciones que nunca ocurrirían naturalmente.…”
Section: Contenido De Sustancias Alelopáticas En Los Lixiviadosunclassified
“…The use of soil cover in the orchards reduces and even eliminates the use of herbicides. The effect of cover plants on weeds may be suppressant by means of plant mass deposition and even allopathic effect with the release of allele chemical that inhibit the growth of weeds (Bettoni et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%